Sharia Banking Dispute Settlement through the Litigation Process - Henri Handal Fifgita (Activa Yuris: Jurnal Hukum, 2022)
This research aims to find out the way to resolve disputes in Islamic Banking through a litigation process. Normative legal research is the method used in this research. This method is to collect the secondary data through literature study by reading the Act, literature book, and the documents that are relative to the topic of this study discussed. The data obtained from the processing of library data was analyzed qualitatively. The treatment of Islamic economic cases, in a simple way, is based on the Regulation of the Supreme Court Number 2 of 2015 concerning the Procedure for a Simple Claims Court. Meanwhile, the handling of Islamic economic cases, in a common way, is based on the applicable Act. In an Islamic economic case by the Party that has made a lawsuit then it can file its lawsuit through the Registrar of the Religious Court of the area where the Plaintiff located or the area where the Defendant is or according to the agreement in the contents of the contract. The trial for examining Islamic economic cases at the Court is open to the public unless otherwise stipulated by law. This is based on the provisions of Article 19 paragraph (1) of Law Number 4 of 2004 that has been changed in Article 13 of Law Number 48 of 2009 concerning Judicial Power. This provision applies to the hearing of the Islamic banking dispute examination, also. In the common trial examination, this Islamic economic dispute occurs when both parties to the dispute or through their proxies are present at the first trial and/or subsequent trial. Before holding the trial, mediation is firstly conducted to find a solution, then the next stage was the examination of the subject matter and the opportunity to answer between the Applicant and Respondent. Based on the provisions of Article 178 HIR / Article 189 RBg, when the case examination is completed, the Panel of Judges, based on their position, conducts deliberation to make a decision to be applied. For the decision of Islamic Banking stating that the Applicant’s claim is accepted, the Respondent can apply to the Appeal before Cassation or Judicial Review.